Sosialisasi dan Pelatihan Penggunaan Aplikasi “BukuWarung” sebagai Alat Pembukuan Keuangan Sederhana Bagi Pelaku UMKM di Kelurahan Tenggilis Mejoyo Surabaya - Dinda Eka Rahmawati; Ratih Mukti Azhar (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The research in this journal has explained that MSMEs in Tenggilis Mejoyo Village face traditional bookkeeping challenges that are prone to errors. To overcome this, socialisation activities and training on the use of the